UPAYA MENINGKATKAN KETERAMPILAN BERBICARA SISWA MELALUI METODE DONGENG DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS III SD NEGERI 107982 LUBUK PAKAM TAHUN PEMBELAJARAN 2024-2025 - Imelda Simanullang; Risnawaty; Sutikno; Rahmat Kartolo; Sri Ulina Beru Ginting (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to improve the speaking skills of third grade students of SD Negeri 107982 Lubuk Pakam through the storytelling learning method. The method used is classroom action research (CAR) with two cycles, each consisting of four stages: planning, action, observation, and reflection. Before the first cycle, a pre-cycle survey was conducted which showed that only 23% of 30 students achieved the Minimum Completion Criteria (KKM) in speaking skills. In the first cycle, storytelling-based learning was carried out and resulted in an increase in students' speaking skills, with 53% of students achieving KKM. In the second cycle, a modification of learning was carried out with paired exercises, which succeeded in increasing the percentage of students achieving KKM to 83%. The storytelling method has been proven to be able to create an interactive and enjoyable learning atmosphere, as well as improve students' verbal and nonverbal aspects, such as intonation, expression, and eye contact. The results of the study indicate that the storytelling method can be an effective strategy in developing students' speaking skills in Indonesian subjects at the elementary school level.